2023
DOI: 10.3389/fgene.2023.1139994
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of novel prognostic biomarkers and therapeutic targets for non-small cell lung cancer

Abstract: Background: Despite the significant survival benefits of anti-PD-1/PD-L1 immunotherapy, non-small cell lung cancer (NSCLC) remains one of the most common tumors and major causes of cancer-related deaths worldwide. Thus, there is an urgent need to identify new therapeutic targets for this refractory disease.Methods: In this study, microarray datasets GSE27262, GSE75037, GSE102287, and GSE21933 were integrated by Venn diagram. We performed functional clustering and pathway enrichment analyses using R. Through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Below is a general methodology for discovering new biomarkers using bioinformatics tools [ 79 , 101 , 102 ]: Genomic data identification: The first step is to gather relevant genomic data for the study. This may include publicly available datasets from genomic databases, such as GenBank or the Human Genome Project Repository, or internally generated data from experiments.…”
Section: Methodology For Discovering Novel Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations
“…Below is a general methodology for discovering new biomarkers using bioinformatics tools [ 79 , 101 , 102 ]: Genomic data identification: The first step is to gather relevant genomic data for the study. This may include publicly available datasets from genomic databases, such as GenBank or the Human Genome Project Repository, or internally generated data from experiments.…”
Section: Methodology For Discovering Novel Biomarkersmentioning
confidence: 99%
“…Protein–protein interaction (PPI) network analysis identified central node genes, and their potential prognostic value was confirmed through survival analysis. The markers predicted in this study are listed below [ 101 ]: ANLN: ANLN is observed to be overexpressed in multiple tumor types, including pancreatic, brain, breast, and lung cancers. It is involved in cell proliferation, and its inhibition can impede cancer cell division, migration, and invasion.…”
Section: Methodology For Discovering Novel Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations